Impacts of Climate Change on Rainfall Trends Under RCP Scenarios in Johor, Malaysia - Rahmat, Siti Nazahiyah; Hamid, Hanafi; Tukimat, Nurul Nadrah Aqilah; Khastagir, Anirban; Al-Gheethi, Adel (International Journal of Integrated Engineering, 2022)
Changes in the spatial and temporal rainfall pattern affected by the climate change need to be investigated as its significant characteristics are often used for managing water resources. In this study, the impacts of climate change on rainfall variability in Johor was investigated by using General Circulation Model (GCM) on the availability of daily simulation for three representative concentration pathways (RCP) scenarios, RCP 2.6, RCP 4.5 and RCP 8.5 for interval year of ?2030, ?2050 and ?2080. In addition, the annual future rainfall trend for the first interval year of ?2030 was also made. Daily rainfall series from eight (8) stations in Johor, Malaysia capturing 30 years period (1988-2017) with less than 10% missing data were chosen. The annual mean rainfall for RCP 2.6, 4.5 and 8.5 was predicted increase by 17.5%, 18.1% and 18.3%, respectively as compared to historical data. Moreover, the Mann-Kendall (MK) test was used to detect the trend and resulted in no trend for RCP 2.6. Even so, RCP 4.5 showed a significant upward trend in Muar and Kota Tinggi, and for RCP 8.5, all regions were detected to have an upwards trend except for Pontian and Kluang. In general, the concentration of greenhouse gases from RCP 8.5 gave the highest rainfall in future.